The battle of life : a love story - Dickens, Charles, 1812-1870 (Floating Press, 2009)
Curl up with this heartwarming tale of redemption from the master of the happy ending, Charles Dickens. A great read at Christmas-time or whenever you could use some uplifting lighter fare, The Battle of Life is a fast-paced tale that you'll finish with a smile on your face and renewed faith in the inherent goodness of humanity.